Writing compelling dialogue for film and TV : the art and craft of raising your voice on screen - Caplin, Loren-Paul (London : Routledge, 2021)
"Writing Compelling Dialogue for Film and TV is a practical guide that provides screenwriters with a clear set of exercises, tools, and methods to raise your ability to hear and discern conversation at a more complex level, in turn allowing you to create better, more nuanced, complex and compelling dialogue. The process of understanding dialogue writing begins with increasing writers' awareness of what they hear. This book provides writers with an assortment of dialogue and language tools, techniques, and exercises and teaches them how to perceive and understand the function, intent and thematic/psychological elements that dialogue can convey about character, tone, and story. Text, subtext, voice, conflict, exposition, rhythm and style are among the many aspects covered. This book reminds us of the sheer joy of great dialogue and will change and enhance the way writers hear, listen to, and write dialogue, and along the way aide the writers' confidence in their own voice allowing them to become more proficient writers of dialogue. Written by veteran screenwriter, playwright, and screenwriting professor Loren-Paul Caplin, Writing Compelling Dialogue is an invaluable writing tool for any aspiring screenwriter who wants to improve their ability to write dialogue for film and television, as well as students, professionals, and educators"--
Keywords: Motion picture authorship; Television authorship; Dialogue in motion pictures; Dialogue in television programs